1510 A Study of the Value of Sleep Eeg Record in Predicting Seizure Recurrence in Children with a Single Afebrile Seizure. (October 2012) - Chukwu, J; Gallagher, P; McCoy, B; Webb, D
Abstract : Aims: The main aim of the study was to determine the value of a sleep EEG recording in predicting the risk of epilepsy in children with a single afebrile seizure. Methods: A retrospective review of 69 children who underwent sleep EEG recordings in 2007 following their first afebrile seizure was undertaken. Parents were sent a questionnaire on seizure recurrence, diagnosis of epilepsy, anti-epileptic medication use, further EEGs and school progress. Results: Fifty two (52) questionnaires (75%) were completed and returned. Twenty three of the fifty two children (44%) have had one or more further seizures - 7/25 (28%) of those with normal sleep EEG recordings and 14/21 (67%) of those who had abnormal sleep EEG recordings. 6/52 (12%) of the respondents had suspicious EEG and 2 of these have had further seizures. 12/21 (57%) of those with abnormal sleep EEGs compared with 5/25(20%) of those with normal EEG have had multiple further seizures. Pearson-Chi Square revealed a significant relationship between abnormal EEG and the development of further seizures (p<0.01). The odds of having further seizures if the EEG was abnormal was 4.9 (95% C.I 1.5–16.1). Conclusions: Sleep EEG is a useful tool in predicting the risk of developing epilepsy in children with first afebrile seizure.